Originally Posted by

**aaaa202** I wonna solve the equation lxl = lyl by using:

sqrt(x^2) = sqrt(y^2)

=>

x^2 = y^2

Here the easiest to do is to use the "zero-rule"

x^2 - y^2 = (x-y)(x+y) = 0

Where it's obvious that x=-y and y=-x etc.

However I don't understand why the same result isnt obtainable by not using this rule for solving the equation. What goes wrong when you do this:

x^2 = y^2

=>

x = (+-)sqrt(y^2)

Where you can't really get any further without comming back to the original statement. What is it that the zero-rules enables you in this case? Like when u factor out and use it instead of dividing by x, which if x=0 is not allowed algebraically.